Growth of Generic E. coli and Aerobic Bacteria on Beef Muscle held at 50°F for 8 Hours - Larry Eubanks; Chad Carr; Chris Pantaleo (EDIS)
AN222, a 4-page fact sheet by Larry Eubanks, Chad Carr, and Chris Pantaleo, presents the results of a study to determine the growth of generic E. coli and aerobic bacteria as indicators of pathogenic bacteria on beef muscle held at 50°F for eight hours. Includes references. Published by the UF Department of Animal Sciences, November 2009.